ISLAMIC FINANCE AND CRISIS MANAGEMENT IN KAZAKHSTAN: LESSONS FROM THE COVID-19 PANDEMIC - Maria Alexandrovna; Sergey Kuznetsov; Viktoria Sokolova (Sharia Oikonomia Law Journal, 2025)
The COVID-19 pandemic exposed structural vulnerabilities in financial systems worldwide, prompting renewed interest in ethical and resilient financing models. In Kazakhstan, where Islamic finance is still nascent, the crisis highlighted both challenges and opportunities for faith-based financial instruments to contribute to national crisis response mechanisms. This study examines the role of Islamic finance in Kazakhstan’s financial resilience during the COVID-19 pandemic, assessing its potential integration into broader economic recovery frameworks. A mixed-methods approach was adopted, combining doctrinal review of Kazakhstan’s Islamic finance legislation with semi-structured interviews involving policymakers, Shariah scholars, and financial practitioners. The findings indicate that while Islamic finance institutions remained limited in size and scope, their emphasis on risk-sharing, social solidarity (zakat, waqf), and asset-backed structures offered valuable alternatives during economic shocks. Islamic microfinance and charitable models proved especially relevant for supporting vulnerable populations. The study concludes that with regulatory development, institutional support, and public awareness, Islamic finance can enhance Kazakhstan’s financial system diversification and crisis response capability. The research contributes to the discourse on ethical finance as a complementary mechanism for economic resilience in emerging markets.